2002
DOI: 10.1006/mthe.2002.0711
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Gene Delivery of IL-1Ra and Soluble TNF Receptor Confers a Distal Synergistic Therapeutic Effect in Antigen-Induced Arthritis

Abstract: Intra-articular expression of antagonists of interleukin-1beta (IL-1beta) and tumor necrosis factor-alpha (TNF-alpha) in arthritic rabbit knee and mouse ankle joints by direct adenoviral-mediated intraarticular delivery results in amelioration of disease pathology in both the treated and contralateral untreated joints. Previous experiments suggest that direct adenoviral infection of resident antigen-presenting cells (APCs) and subsequent traveling of these cells to other sites of inflammation and lymph nodes m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 33 publications
1
38
0
Order By: Relevance
“…39,40 Recently, it has been reported that local gene transfer could result in a systemic therapeutic effect without systemic elevation of the therapeutic protein. 19,41 Further investigation on the mechanism responsible for these phenomena may help to develop the clinically relevant protocol for electroporation-based gene delivery strategy for the treatment of human RA.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Recently, it has been reported that local gene transfer could result in a systemic therapeutic effect without systemic elevation of the therapeutic protein. 19,41 Further investigation on the mechanism responsible for these phenomena may help to develop the clinically relevant protocol for electroporation-based gene delivery strategy for the treatment of human RA.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our observation, it was reported that a contralateral therapeutic effect was achieved even though significant levels (41 ng/ml) of soluble TNFa receptor or IL-1Ra were not detected in animal fluids by ELISA. 36,37 It was suggested that certain kinds of transduced cells might play an important role(s) in contralateral therapeutic effects. 36 Furthermore, it was also reported that dendritic cells could be transfected by intramuscular injection of plasmid DNA and that the transfected dendritic cells could modulate the immune responses.…”
Section: Il-1ra Dna Injection Inhibits Cia J-m Kim Et Almentioning
confidence: 99%
“…The contralateral effect was first observed following injection of adenoviral vectors expressing IL-1and sTNF soluble receptors 7 and has been more recently observed following intra-articular gene transfer of IL-4, 19 FasL, 20 IL-1Ra, 9 and NF-kB decoy oligonucleotides. 10 Hypothetically, the contralateral effect could be conferred by several mechanisms including leakage of virus from the injected joint, generalized immunosuppression due to overexpression of transgene product, migration of genetically modified or functionally altered cells or through a neurogenic pathway.…”
Section: Discussionmentioning
confidence: 97%
“…8 In addition, the ex vivo gene transfer of IL-1Ra and soluble TNF-a receptor either alone or in combination using genetically modified autologous synovial fibroblasts transplanted intra-articularly was shown to confer a contralateral effect in contralateral control joints, demonstrating that the remedial effects conferred to distant joints do not require direct in vivo delivery of genes. 9 In addition, administration of NF-kB deoxyoligonucleotides/liposome complexes into rat knee joints, able to block TNF and IL-1 expression by macrophages and dendritic cells (DC), conferred a contralateral therapeutic effect in untreated inflamed knee joints. 10 Taken together, these results suggest that the contralateral effect is not restricted to any particular delivery vector, anti-inflammatory/immunosuppressive gene product or arthritis model.…”
Section: Introductionmentioning
confidence: 99%